Glutamic acid assisted hydrolysis strategy for preparing prebiotic xylooligosaccharides - Huang, Rong; Zhang, Rui; Yao, Shuangquan; Si, Mengyuan; Xia, Ruowen; Zhou, Xin; Fan, Xingli; Jiang, Kankan (Frontiers in Nutrition, 2022)
Since the immune-boosting properties as well as the benefit of promoting the growth of gut bacteria, xylooligosaccharides as prebiotics have attracted considerable interest as functional feed additives around the world. A growing number of studies suggest that acidic hydrolysis is the most cost-effective method for treating xylan materials to prepare xylooligosaccharides, and organic acids were proved to be more preferable. Therefore, in this study, glutamic acid, as an edible and nutritive organic acid, was employed as a catalyst for hydrolyzing xylan materials to prepare xylooligosaccharides. Further, xylooligosaccharide yields were optimized using the response surface methodology with central composite designs. Through the response surface methodology, 28.2 g/L xylooligosaccharides with the desirable degree of polymerization (2-4) at a yield of 40.5 % could be achieved using 4.5% glutamic acid at 163°C for 41 min. Overall, the application of glutamic acid as a catalyst could be a potentially cost-effective method for producing xylooligosaccharides.